Can clot density predict recanalization in acute ischemic stroke treated with intravenous tPA?. Issue 1 (13th September 2017) - Bouchez, Laurie; Altrichter, Stephen; Pellaton, Alain; Ouared, Rafik; Kulcsar, Zsolt; Sztajzel, Roman; Platon, Alexandra; Machi, Paolo; Poletti, Pierre-Alexandre; Lövblad, Karl-Olof
Stroke has become an absolute emergency that is treated by additional endovascular means or by replacing pharmacological options. Modern neuroradiological techniques such as computed tomography (CT) allow us to examine multiple parameters of the diseased brain. These focused on the parenchyma and hemodynamics for pretherapeutic decisions. However, it has become evident that the clot is the current target for interventional measures. Clot length is established as a marker for recanalization. The dense artery sign is known as an acute CT sign of stroke that is readily visible on acute nonenhanced CT. The rationale behind our study was to study if clot density might represent clot vulnerability or resistance to treatment. We conducted a prospective study of all consecutive stroke patients admitted to our hospital over 1 year, who presented with signs of acute middle cerebral artery stroke within the therapeutic window, and who underwent either intravenous or combined intravenous and intra-arterial thrombolysis. All patients were evaluated with a complete stroke CT protocol, transcranial color-coded duplex sonography monitoring, and clinical evaluation with the National Institutes of Health Stroke Scale (NIHSS) score. We measured clot length using planimetry on unenhanced CT and measured Hounsfield units in the clots on the same images. A total of 31 patients were included in the study (19 men, 12 women, aged 35–90 years). We found that patients with a longer clot on the unenhanced CT had a higher NIHSS score, confirming previous literature. However, we found that patients with a lower clot density recanalized to a more marked degree and had a better clinical outcome. Patients who did not recanalize had a higher clot density (49 Hounsfield units) than those who did recanalize (23 Hounsfield units). Overall, measuring the clot seems to be an important additional parameter to be taken into account. In our study, CT clot density seems to correlate with clinical outcome and recanalization. The higher density seems to represent a higher red blood cell content. This is evidence that clot composition could play a much more important role in acute stroke than thought until now and characterizing it with imaging may help in choosing the adequate treatment modality. Higher density seems to reflect erythrocyte content. Therefore, patients with a longer and denser clot may necessitate direct thrombectomy.